2019
DOI: 10.1002/cite.201900121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spacing of Multiple Impellers on Power Input in an Industrial‐Scale Aerated Stirred Tank Reactor

Abstract: Despite the fact that aerated stirred tank reactors are widely used in industry and often studied, their design and scale‐up still remains challenging. Especially the specific power input is a crucial and geometry‐dependent scale‐up parameter, usually calculated with the dimensionless power number Po. Within the scope of this study, the power number is measured for different stirrer types and configurations in a laboratory and an industrial‐scale aerated stirred tank reactor. Good agreements to literature are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…In respect to the described bubble formation behavior, the gas utility is compared at a k L a of 60 1/h and 160 1/h, resulting in applied vvm of 0.05 up to 0.67 for the sintered frit and 1 µm SPG aerator. In contrast to the microbubble aerators, higher gassing rates of 16.67 vvm (5 mm open pipe) and 8.44 vvm (6 × 0.5 mm open pipe) is necessary to achieve a k L a of 160 1/h, which would be uneconomic in process scale‐up (Fitschen et al, 2019; Garcia‐Ochoa & Gomez, 2009). Nevertheless, both macrobubble aerators are resulting in more reasonable flow rates at a k L a of 60 1/h with 2.23 vvm (5 mm open pipe) and 0.5 vvm (6 × 0.5 mm open pipe).…”
Section: Resultsmentioning
confidence: 99%
“…In respect to the described bubble formation behavior, the gas utility is compared at a k L a of 60 1/h and 160 1/h, resulting in applied vvm of 0.05 up to 0.67 for the sintered frit and 1 µm SPG aerator. In contrast to the microbubble aerators, higher gassing rates of 16.67 vvm (5 mm open pipe) and 8.44 vvm (6 × 0.5 mm open pipe) is necessary to achieve a k L a of 160 1/h, which would be uneconomic in process scale‐up (Fitschen et al, 2019; Garcia‐Ochoa & Gomez, 2009). Nevertheless, both macrobubble aerators are resulting in more reasonable flow rates at a k L a of 60 1/h with 2.23 vvm (5 mm open pipe) and 0.5 vvm (6 × 0.5 mm open pipe).…”
Section: Resultsmentioning
confidence: 99%
“…For the measurement of the power number, a motor (ViscoPaktRheo X7, HiTec Zang, Germany) with integrated torque sensor is used. A detailed description of the methodology and the data evaluation is given in [32].…”
Section: Methodsmentioning
confidence: 99%
“…With their adapted magnetic system, Suleiko et al ( 2020 ) demonstrated a drive with a torque of 200 Nm that is suitable for biological applications at a scale of 15 m 3 . ZETA’s magnetic bottom-mounted agitator for bioreactors with a torque of more than 400 Nm was also evaluated at the same scale (ZETA GmbH n.d. ; Rosseburg et al 2018 ; Fitschen et al 2019 ), delivering results that predict applicability at scales up to 30 m 3 (ZETA GmbH 2020a ). Although their initial industrial use was controversial because of biological (hygienic design and SIP/CIP capability), mechanical, and chemical safety (possible abrasion in bearing-based systems) concerns, as well as the early lack of speed and torque monitoring (Eibl et al 1996 ), magnetic agitators have been able to gain more and more acceptance, as a result of increased qualification and validation.…”
Section: Drive Systems and Seals Commonly Used In Biotechnological Prmentioning
confidence: 99%